Genetic Basis of Phenotypic Differences Between Chinese Yunling Black Goats and Nubian Goats Revealed by Allele-Specific Expression in Their F1 Hybrids - Cao, Yanhong; Xu, Han; Li, Ran; Gao, Shan; Chen, Ningbo; Luo, Jun; Jiang, Yu (Frontiers in Genetics, 2019)
Chinese Yunling black goats and African Nubian goats are divergent breeds showing significant differences in body size, milk production, and environmental adaptation. However, the genetic mechanisms underlying these phenotypic differences remain to be elucidated. In this report, we provide a detailed portrait of allele-specific expression (ASE) from 54 RNA-Seq analyses across six tissues from nine F1 hybrid offspring generated by crossing the two breeds combined with 13 genomes of the two breeds. We identified a total of 524 genes with ASE, which are involved in bone development, muscle cell differentiation, and the regulation of lipid metabolic processes. We further found that 38 genes with ASE were also under directional selection by comparing 13 genomes of the two breeds; these 38 genes play important roles in metabolism, immune responses, and the adaptation to hot and humid environments. In conclusion, our study shows that the exploration of genes with ASE in F1 hybrids provides an efficient way to understand the genetic basis underlying the phenotypic differences of two diverse goat breeds.